2020
DOI: 10.25139/ijair.v2i2.3030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clustering K-Means, Fuzzy C-Means, and Linkage for Nasa Active Fire Dataset

Abstract: One of the causes of forest fires is the lack of speed of handling when a fire occurs. This can be anticipated by determining how many extinguishing units are in the center of the hot spot. To get hotspots, NASA has provided an active fire dataset. The clustering method is used to get the most optimal centroid point. The clustering methods we use are K-Means, Fuzzy C-Means (FCM), and Average Linkage. The reason for using K-means is a simple method and has been applied in various areas. FCM is a partition-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Subsequently, the curve provided information about the number of clusters used. For example, when the value of the rst and second gave the angle on the graph or the value that had decreased the most, the number can be used (Kurniawan et al, 2020) . 3.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the curve provided information about the number of clusters used. For example, when the value of the rst and second gave the angle on the graph or the value that had decreased the most, the number can be used (Kurniawan et al, 2020) . 3.…”
Section: Methodsmentioning
confidence: 99%
“…Surya Narayana and Vasumathi proposed new attributes similarity-based K-Medoids clustering technique that achieved better clustering results than traditional K-Medoids algorithm [41]. In their study, Kurniawan et al also compared K-Means and Fuzzy C-Means with another clustering algorithm, linkage, for the NASA active fire dataset and found that Fuzzy C-Means produced better clustering results [42]. On the other hand, Zhou and Yang investigated the effect of cluster size distribution on clustering and compared K-Means and Fuzzy C-Means algorithms [43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research that uses data mining to create clusters in dataset analysis, including the Fuzzy C-Means Algorithm [12]- [14], Multifactor Evaluation Process (MFEP) [15], Comparison of Single Linkage, Complete Linkage and Average Linkage Clustering Methods [16] [14], and K-Means Algorithm [14] [17]by Using Particle Swarm [18]. However, no one has discussed the paper to make groupings know the level of student satisfaction with online learning.…”
Section: Introduction Coronavirus (Covid 19mentioning
confidence: 99%